2021
DOI: 10.1186/s12958-021-00757-6
|View full text |Cite
|
Sign up to set email alerts
|

Does mRNA SARS-CoV-2 vaccine influence patients' performance during IVF-ET cycle?

Abstract: Objective No information exists in the literature regarding the effect of mRNA SARS-CoV-2 vaccine on subsequent IVF cycle attempt. We therefore aim to assess the influence of mRNA SARS-CoV-2 vaccine on IVF treatments. Design An observational study. Setting A tertiary, university-affiliated medical center. Patients and Methods All couples undergoing consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
131
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(156 citation statements)
references
References 20 publications
9
131
0
6
Order By: Relevance
“…12,13 To date, only two Israeli studies have focused on the potential correlation between messenger ribonucleic acid (mRNA) COVID-19 vaccine and in vitro fertilization (IVF) outcomes. 14,15 Similar results were found in ovarian response and embryological characteristics between vaccinated and control groups, and one study further reported an acceptable pregnancy rate of 30% in vaccinated women. 15 The authors thus concluded that mRNA COVID-19 vaccine did not influence patients' performance during IVF treatment.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…12,13 To date, only two Israeli studies have focused on the potential correlation between messenger ribonucleic acid (mRNA) COVID-19 vaccine and in vitro fertilization (IVF) outcomes. 14,15 Similar results were found in ovarian response and embryological characteristics between vaccinated and control groups, and one study further reported an acceptable pregnancy rate of 30% in vaccinated women. 15 The authors thus concluded that mRNA COVID-19 vaccine did not influence patients' performance during IVF treatment.…”
Section: Introductionsupporting
confidence: 59%
“…14,15 Similar results were found in ovarian response and embryological characteristics between vaccinated and control groups, and one study further reported an acceptable pregnancy rate of 30% in vaccinated women. 15 The authors thus concluded that mRNA COVID-19 vaccine did not influence patients' performance during IVF treatment. Nonetheless, both studies are of small sample size (<50), and there is still a lack of real-world data on the follow-up of inactivated vaccine administration among infertile patients.…”
Section: Introductionsupporting
confidence: 59%
“…For people in the reproductive age group or planning pregnancy, the effect of the COVID-19 vaccine is an important consideration. Fortunately, based on multiple reports, no evidence of an adverse effect on the fertility of women or men has been found [115][116][117][118][119][120].…”
Section: Impact Of Covid-19 Vaccine On Fertilitymentioning
confidence: 99%
“…Similarly, an assessment of follicular steroidogenesis and oocyte quality did not show any measurable difference when compared with unvaccinated women ( Bentov et al , 2021 ). Moreover, Orvieto et al (2021) reported that many IVF treatment parameters, such as the number of oocytes and mature oocytes retrieved, fertilization rate and the ratio of top-quality embryos (TQEs) per fertilized oocyte, did not significantly differ between the pre- and post-BNT162b2 vaccination groups ( Orvieto et al , 2021 ): these researchers had also found that COVID-19 infection could lead to a significantly lower proportion of TQEs ( Orvieto et al , 2021 ). Overall, these primary findings unanimously indicate that vaccination will not result in any measurable detrimental effect on the female or male reproductive system.…”
Section: Impact Of Mrna Vaccination On Human Fertilitymentioning
confidence: 99%